Pancasila and Islamic Religious Education as Philosophical Foundations: Reforming National Criminal Law through Islamic Sociological Jurisprudence Theory: Pancasila dan Pendidikan Agama Islam Sebagai Landasan Filosofis: Reformasi Hukum Pidana Nasional Melalui Teori Fikih Sosiologi Islam - Rifania Halimatussakdiah; Hikma Paujia; Kamelia Maimunah; Ahmad Muhamad Mustain Nasoha (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2026)
The reform of national criminal law is an urgent necessity to realize a legal system that is just, humane, and contextual with Indonesian values. This article aims to analyze the role of Pancasila and Islamic Religious Education (IRE) as the philosophical foundation in the national criminal law system through sociological Islamic jurisprudence. The research method used is juridical-normative with conceptual and sociological approaches. The results show that Pancasila’s values, such as social justice, humanity, and belief in God, align substantially with Islamic legal principles emphasizing public interest, justice, and human rights. However, implementation is often hindered by legal formalism and political intervention that prioritize procedural certainty over substantive justice. Sociological Islamic jurisprudence asserts that law must develop according to social realities and religious values of society. Therefore, integrating Pancasila and IRE in criminal law formation provides normative legitimacy and increases social acceptance of the law. This article concludes that national criminal law reform based on Pancasila and the Islamic sociological approach can realize an adaptive, just legal system with Indonesian character.